Extracellular matrix stiffness—The central cue for skin fibrosis - Wang, Kang; Wen, Dongsheng; Xu, Xuewen; Zhao, Rui; Jiang, Feipeng; Yuan, Shengqin; Zhang, Yifan; Gao, Ya; Li, Qingfeng (Frontiers in Molecular Biosciences, 2023)
Skin fibrosis is a physiopathological process featuring the excessive deposition of extracellular matrix (ECM), which is the main architecture that provides structural support and constitutes the microenvironment for various cellular behaviors. Recently, increasing interest has been drawn to the relationship between the mechanical properties of the ECM and the initiation and modulation of skin fibrosis, with the engagement of a complex network of signaling pathways, the activation of mechanosensitive proteins, and changes in immunoregulation and metabolism. Simultaneous with the progression of skin fibrosis, the stiffness of ECM increases, which in turn perturbs mechanical and humoral homeostasis to drive cell fate toward an outcome that maintains and enhances the fibrosis process, thus forming a pro-fibrotic "positive feedback loop". In this review, we highlighted the central role of the ECM and its dynamic changes at both the molecular and cellular levels in skin fibrosis. We paid special attention to signaling pathways regulated by mechanical cues in ECM remodeling. We also systematically summarized antifibrotic interventions targeting the ECM, hopefully enlightening new strategies for fibrotic diseases.